Foreword: Marx and the radical criticism - Gómez Osorio, Juan David (Estudios de Filosofía, 2020)
Among the many attempts to invalidate the thought of Karl Marx, perhaps the most effective in theoretical terms has been precisely to give the thinker his place in the history of ideas: it is said that he is an important critic of the market economy, whose reasoning was mostly applicable to 19th-century capitalism. But, in the face of the transformations and economic, political and, ultimately, human advances of contemporary capitalism, its concepts and reflections became obsolete for the present. In response to this attitude, numerous theorists have demonstrated that as long as the contradiction between wage labor and capital—a nodal point of Marx’s economic analysis—continues to be at the basis of the system of social production, the critique of the critique of Marxist political economy will continue being actual. Regardless of whether the worker looks like the 19th-century proletarian, the 20th-century office worker, or the freelancer of the 21st century.